Dr. Audrey Holland's Crazy Patchwork Quilt: A Thematic Analysis - Richardson, Jessica D.; Dalton, Sarah Grace Hudspeth; Hubbard, Honey Isabel; Henry, Maya (Seminars in Speech and Language, 2024)
Dr. Audrey Holland was a friend to people with aphasia and related disorders, care partners, community advocates, students, clinicians, educators, researchers, and more. Her profound impact extended across these diverse communities within aphasiology and speech-language pathology. Through her words and deeds, Audrey established a rich legacy that continues to guide and inspire countless individuals. A careful examination of her contributions reveals a roadmap for those seeking to embark on a similar journey of compassion and influence. To pay tribute to our mentor and friend, we conducted a thematic analysis of her solo works to identify enduring themes, laugh-out-loud anecdotes, and poignant insights to share with her friends, colleagues, mentees, and even strangers who, after reading this article, will be touched and changed by her wisdom.
Keywords: aphasia; caregiver; coaching; life participation; resilience